2010
DOI: 10.1007/s00402-010-1064-9
|View full text |Cite
|
Sign up to set email alerts
|

Varus malalignment has no influence on clinical outcome in midterm follow-up after total knee replacement

Abstract: The present data do not support the assumption that there is a correlation between varus malalignment and a bad medium-term radiological and clinical outcome after total knee arthroplasty. This questions the indication for revision of painful and varus malaligned prostheses, since an improvement of the clinical outcome is not to be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
121
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 23 publications
9
121
1
3
Order By: Relevance
“…The same applied for KSS and ROM, where the differences were small and hardly clinically relevant (Table 2, see supplementary data, and Table 4). This is in agreement with the results of Matziolis et al (2010), who reported that postoperative varus malalignment as compared to neutral knee alignment after TKA had no influence on clinical outcome (KSS, the WOMAC, and the SF36). Furthermore, Magnussen et al (2011) even found KSS to be better in patients with residual varus than in those with neutral alignment.…”
Section: Discussionsupporting
confidence: 92%
“…The same applied for KSS and ROM, where the differences were small and hardly clinically relevant (Table 2, see supplementary data, and Table 4). This is in agreement with the results of Matziolis et al (2010), who reported that postoperative varus malalignment as compared to neutral knee alignment after TKA had no influence on clinical outcome (KSS, the WOMAC, and the SF36). Furthermore, Magnussen et al (2011) even found KSS to be better in patients with residual varus than in those with neutral alignment.…”
Section: Discussionsupporting
confidence: 92%
“…Our subgroup comparisons of the functional outcomes of aligned knees and outliers may provide some clues to resolving recent debate as to whether the restoration of neutral limb alignment is associated with better functional outcome [4,23,32]. Several authors have recently challenged the importance of the restoration of neutral limb alignment [4,23,32].…”
Section: Discussionmentioning
confidence: 89%
“…Several authors have recently challenged the importance of the restoration of neutral limb alignment [4,23,32]. A previous study that compared aligned and varus-malaligned knees found no differences between the two in terms of American Knee Society, WOMAC, or SF-36 scores [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parratte et al [67] found mechanical alignment in 292 TKAs did not confer a significant advantage compared to malalignment (± 3°) in 106 cases in terms of survival. In a smaller study, Matziolis et al [57] reported no difference in patient outcome between aligned TKA and a subset of varus outliers and no revisions in either group. Nevertheless, their findings implied not that coronal alignment was unimportant but rather that assessment of alignment as a dichotomous variable (aligned versus malaligned) was limited and could only serve as a general guideline.…”
Section: Discussionmentioning
confidence: 93%